2008
DOI: 10.1590/s0103-50532008000700013
|View full text |Cite
|
Sign up to set email alerts
|

Type II photooxidation mechanism of biomolecules using chloro (5,10,15,20-Tetraphenylporphyrinato) indium (III) as a photosensitizer

Abstract: Foi determinado o mecanismo de fotooxidação de albumina de soro bovino (BSA), L-triptofano (Trp) e células vermelhas do sangue (RBC) por cloro (5,10,15,20-tetrafenilporfirinato) de índio(III) (InTPP). A velocidade de fotooxidação de Trp, BSA e RBC por InTPP foi diminuída na presença de NaN 3 . A presença de D 2 O aumentou a velocidade de fotooxidação de Trp e BSA e diminuiu a de RBC. Esta diminuição provavelmente está correlacionada com a redução da constante de associação entre InTPP e RBC na presença de D 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The formed ROS initiate a cascade of events that result in reduction or oxidation of vital components (e.g., proteins and lipids) in the cellular compartment of the cancerous tissue and thereby cause cell death and tumor eradication. Numerous studies have suggested that the PDT toxicity in the cells is mainly mediated by singlet oxygen which dominates the ROS profile (type II mechanism). In the type II mechanism, the photosensitizer in the excited triplet state can interact with ground state oxygen molecules, generating singlet oxygen through an energy transfer process. , An alternative route is the type I mechanism in which the photosensitizer in the excited triplet state can interact directly with the substrate and/or solvent through electron or proton transfer processes. This leads to generation of charged or neutral radicals, which quickly react with oxygen molecules to produce ROS such as superoxide (O 2 −• ) and hydroxyl (OH • ) radicals and hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formed ROS initiate a cascade of events that result in reduction or oxidation of vital components (e.g., proteins and lipids) in the cellular compartment of the cancerous tissue and thereby cause cell death and tumor eradication. Numerous studies have suggested that the PDT toxicity in the cells is mainly mediated by singlet oxygen which dominates the ROS profile (type II mechanism). In the type II mechanism, the photosensitizer in the excited triplet state can interact with ground state oxygen molecules, generating singlet oxygen through an energy transfer process. , An alternative route is the type I mechanism in which the photosensitizer in the excited triplet state can interact directly with the substrate and/or solvent through electron or proton transfer processes. This leads to generation of charged or neutral radicals, which quickly react with oxygen molecules to produce ROS such as superoxide (O 2 −• ) and hydroxyl (OH • ) radicals and hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested that the PDT toxicity in the cells is mainly mediated by singlet oxygen which dominates the ROS profile (type II mechanism). [6][7][8][9] In the type II mechanism, the photosensitizer in the excited triplet state can interact with ground state oxygen molecules, generating singlet oxygen through an energy transfer process. 10,11 An alternative route is the type I mechanism in which the photosensitizer in the excited triplet state can interact directly with the substrate and/or solvent through electron or proton transfer processes.…”
Section: Introductionmentioning
confidence: 99%